2018
DOI: 10.1002/open.201800172
|View full text |Cite
|
Sign up to set email alerts
|

Spaced TiO2 Nanotubes Enable Optimized Pt Atomic Layer Deposition for Efficient Photocatalytic H2 Generation

Abstract: In the present work, we report the use of TiO2 nanotube (NT) layers with a regular intertube spacing that are decorated by Pt nanoparticles through the atomic layer deposition (ALD) of Pt. These Pt‐decorated spaced (SP) TiO2 NTs are subsequently explored for photocatalytic H2 evolution and are compared to classical close‐packed (CP) TiO2 NTs that are also decorated with various amounts of Pt by using ALD. On both tube types, by varying the number of ALD cycles, Pt nanoparticles of different sizes and areal den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…Clearly, both HNT and Pt−HNT show a strong increase in their photocatalytic H 2 evolution rate for increasing annealing temperatures up to 500 °C, whereas for higher temperatures the activity drops again. The inset shows corresponding data taken from literature obtained for a similar Pt loading on anodic TiO 2 −NT arrays and for anatase nanopowder (Sigma) . Also for these morphologies a maximum activity for the non‐platinized as well as the platinized samples was obtained at 500 °C.…”
Section: Figuresupporting
confidence: 90%
“…Clearly, both HNT and Pt−HNT show a strong increase in their photocatalytic H 2 evolution rate for increasing annealing temperatures up to 500 °C, whereas for higher temperatures the activity drops again. The inset shows corresponding data taken from literature obtained for a similar Pt loading on anodic TiO 2 −NT arrays and for anatase nanopowder (Sigma) . Also for these morphologies a maximum activity for the non‐platinized as well as the platinized samples was obtained at 500 °C.…”
Section: Figuresupporting
confidence: 90%
“…Under solar light, amounts of 10.53 µL/h (for ten ALD cycles) and 9.41 µL/h (for two cycles) are observed. These results demonstrate the importance of optimized architectures for plasmonic photocatalysis with much higher photocatalytic performances observed in the spaced out nanotubes with smaller Pt nanoparticles (via lesser cycles) [ 273 ] versus the common architecture of closely packed nanotubes [ 272 ].…”
Section: Exploiting Hot Electronsmentioning
confidence: 99%
“…Schmuki et al have demonstrated that single component ALD deposited Pt–TiO 2 nanotubes show high efficiencies for H 2 production under solar and UV light [ 272 ]. A second study, involving a slightly modified architecture of spaced TiO 2 nanotubes in contrast to closely packed TiO 2 nanotubes decorated with Pt nanoparticles via ALD deposition, highlights better performance efficiencies for H 2 generation and the importance of optimized architectures for plasmonic photocatalysis [ 273 ]. Here, amounts of 171.6 µL/h (for ten ALD cycles) and 150.75 µL/h (for two cycles) are observed under UV light.…”
Section: Exploiting Hot Electronsmentioning
confidence: 99%
“…Here, we employ TiO 2 nanotubular arrays with controlled spacing that allow a superior utilization of the tube walls and yield enhanced electrochemical performance. 32,33 Regarding the catalyst material used in PEMFCs, Pt is considered the standard (due to its high catalytic activity 3 ) for both hydrogen oxidation reaction (HOR) at the anode and oxygen reduction reaction (ORR) at the cathode. However, better deposition techniques are necessary, in view of enabling a conformal coating with a minimum loading of Pt while also providing a high dispersion on the catalyst support without interfering with the performance or durability of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…3 Especially, on complex nanostructures, it is hard to achieve uniform and well-dispersed Pt particles with precisely controlled size and quantity by traditional deposition techniques, 34−37 whereas atomic layer deposition (ALD) leads to uniform, highly dispersed deposition on complex nanostructures and allows for a controlled loading amount by varying the number of ALD cycles. 32,38,39 Another crucial aspect of PEMFC technology is the preparation technique of the MEA. The most frequently used techniques are the (a) decal transfer method (DTM), (b) catalyst-coated substrate (CCS), and (c) catalyst-coated membrane (CCM).…”
Section: Introductionmentioning
confidence: 99%